2010
DOI: 10.1159/000321475
|View full text |Cite
|
Sign up to set email alerts
|

Alopecic and Aseptic Nodules of the Scalp (Pseudocyst of the Scalp): A Prospective Clinicopathological Study of 15 Cases

Abstract: Background: Alopecic and aseptic nodules of the scalp (AANS) is a new entity reported first in Japan as ‘pseudocyst of the scalp’. Only retrospective studies have been published. Objectives: To describe the clinicopathological features of AANS (pseudocyst), to evaluate the response to doxycycline and to compare the results to those obtained from patients with dissecting cellulitis of the scalp (DCS). Methods: Fifteen patients with AANS and 7 with DCS were prospectively included. A puncture and a biopsy were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 10 publications
1
65
1
Order By: Relevance
“…Pseudocyst formation was always found in PCS but not in AANS, although granulomatous infiltration was found in both [1,5]. Pseudocyst formation was found in only 4 patients in this study, which is contrary to the previous assumption that racial differences affect pseudocyst formation [5].…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…Pseudocyst formation was always found in PCS but not in AANS, although granulomatous infiltration was found in both [1,5]. Pseudocyst formation was found in only 4 patients in this study, which is contrary to the previous assumption that racial differences affect pseudocyst formation [5].…”
Section: Discussioncontrasting
confidence: 88%
“…The mean disease duration was longer in patients with than without pseudocyst formation in this study (median, 10.3 and 6.4 months, respectively), which might partially explain the inconsistency in the formation of pseudocysts. PCS was reported to occur between the top and forehead area of the scalp [1], whereas other studies showed lesions on the vertex and upper occipital area [2,5,7]. The most commonly involved site in this study was similar to that of AANS rather than PCS.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations